2021
DOI: 10.21037/atm-21-471
|View full text |Cite
|
Sign up to set email alerts
|

ENO3 promoted the progression of NASH by negatively regulating ferroptosis via elevation of GPX4 expression and lipid accumulation

Abstract: Background: ENO3 expression is upregulated in Non-alcoholic fatty liver disease (NAFLD) patient tissues, demonstrated that ENO3 might play crucial roles in NAFLD. However, the mechanism of ENO3 in NAFLD remains unclear. Therefore, this study aimed to investigate the regulatory mechanism of ENO3 in the progression of non-alcoholic steatohepatitis (NASH) in vivo and vitro NASH model. Methods: In vivo and vitro NASH model were established by methionine-choline deficient (MCD)-diet feeding and high free fatty acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 46 publications
(47 reference statements)
3
20
0
Order By: Relevance
“…2J, Lancaster p<0.05) with 129 overlapping with the F 1 WT HFD vs TG HFD males (p=0.06; Fig 2 x ). We identified 12 genes that showed transgenerational deregulated expression across the F 0 -F 2 , (WT HFD vs TG HFD), including Eno3 which has been implicated in glycogen storage [77, 78], Med23 which regulates insulin responsiveness [79], and Prmt1 an epigenetic regulator implicated in liver glucose metabolism [8082]. The number of differentially expressed genes increased every generation in comparisons between the WT HFD and the TG HFD (F 0 =524, F 1 =961, F 2 = 2,141).…”
Section: Resultsmentioning
confidence: 99%
“…2J, Lancaster p<0.05) with 129 overlapping with the F 1 WT HFD vs TG HFD males (p=0.06; Fig 2 x ). We identified 12 genes that showed transgenerational deregulated expression across the F 0 -F 2 , (WT HFD vs TG HFD), including Eno3 which has been implicated in glycogen storage [77, 78], Med23 which regulates insulin responsiveness [79], and Prmt1 an epigenetic regulator implicated in liver glucose metabolism [8082]. The number of differentially expressed genes increased every generation in comparisons between the WT HFD and the TG HFD (F 0 =524, F 1 =961, F 2 = 2,141).…”
Section: Resultsmentioning
confidence: 99%
“…Ferroptosis is associated with the processes of lipid synthesis, storage and degradation ( Li and Li, 2020 ). Moreover, a previous study confirmed that GPX4 (a key regulator of ferroptosis) promotes lipid deposition in L-02 cells ( Lu et al, 2021 ). In this study, our data indicate that inhibition of ferroptosis by Fer-1 (an inhibitor of ferroptosis) and Que decreased both lipid peroxidation and lipid droplet accumulation.…”
Section: Discussionmentioning
confidence: 67%
“…In terms of liver damage, targeting ferroptosis is found to have an effect on relieving or aggravating the symptoms, indicating the role of iron, lipid and amino acid metabolisms. Non-alcoholic fatty liver disease (NAFLD), like non-alcoholic steatohepatitis (NASH), can be promoted by iron accumulation, lipid peroxidation, GPX4 depletion and inflammatory initiation, which are main processes of ferroptosis [ 99 101 ]. After given ferroptosis inhibitors, such as liproxstatin-1 or ferrostatin-1, NASH is greatly alleviated [ 102 , 103 ].…”
Section: Prospectmentioning
confidence: 99%